Literary and Cultural Alternatives to Modernism : Unsettling Presences - Boyiopoulos, Kostas [Ed.]; Patterson, Anthony [Ed.]; Sandy, Mark [Ed.] (New York : Routledge, 2019)
Our collection of essays re-evaluates the much critically contested term of Modernism that, eventually, came to be used of the dominant, or paradigmatic, strain of literary discourse in early-twentieth-century culture. Modernism as a category is one which is constantly challenged, hybridised, and fractured by voices operating from inside and outside the boundaries it designates. These concerns are reflected by those figures addressed by our contributors chapters, which include Rupert Brooke, G. K. Chesterton, E.M. Forster, Thomas Hardy, M. R. James, C.L.R James, Vernon Lee, D.H. Lawrence, Richard La Galliene, Pamela Colman Smith, Arthur Symons, and H.G. Wells. Alert to these disturbing voices or unsettling presences that vex accounts of an emergent Modernism in late nineteenth-century and early twentieth-century literary cultures predominately between 1890-1939, our volume questions traditional critical mappings, taxonomies, and periodisations of this vital literary cultural moment. Our volume is equally sensitive to how the avant garde felt for those living and writing within the period with a view to offering a renewed sense of the literary and cultural alternatives to Modernism.
Keywords: Modernism (Literature) -- Great Britain; English literature -- 20th century -- History and Criticism